2009
DOI: 10.17221/100/2008-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Norway spruce (Picea abies [L.] Karst.) embryogenic tissue to penicillin, carbapenem and aminoglycoside antibiotics

Abstract: Somatic embryogenesis is conveniently utilized for the preparation of Norway spruce (Picea abies [L.] Karst.) transgenic clones by means of Agrobacterium. The establishment of successful transformation protocol requires to determine the tolerance of growing embryogenic tissue to antibiotics in culture and selective media. In 5 Norway spruce lines (genotypes) differences in the tolerance of embryogenic tissues to penicillin antibiotics (amoxicillin, carbenicillin, and ticarcillin), carbapenem antibiotic (merope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…We verified in previous experiments that a sufficient concentration of kanamycin for the selection of spruce transformed embryogenic tissues is 25 mg·l -1 (Malá et al 2009) and that the timentin concentration of 400 mg·l -1 followed by cefotaxime 200 mg·l -1 reliably kills Agrobacterium in the course of a few months. The absence of bacteria was confirmed by Pcr.…”
Section: Resultssupporting
confidence: 70%
“…We verified in previous experiments that a sufficient concentration of kanamycin for the selection of spruce transformed embryogenic tissues is 25 mg·l -1 (Malá et al 2009) and that the timentin concentration of 400 mg·l -1 followed by cefotaxime 200 mg·l -1 reliably kills Agrobacterium in the course of a few months. The absence of bacteria was confirmed by Pcr.…”
Section: Resultssupporting
confidence: 70%
“…This is an important advantage because some P. abies ET cultures progressively lose their maturation potency already after 6 months (Högberg et al, 1998). According to Walter et al (1999), the non-transformed tissue of Picea abies is highly resistant to kanamycin but our results (Malá et al, 2009) showed that kanamycin concentrations of 50 mg/l and 100 mg/l appeared toxic in all lines used. Therefore, 25 mg kanamycin/l was applied as a starting selection concentration.…”
Section: Resultsmentioning
confidence: 59%